Hassan Fathy. Architecture for the poor. Chicago ; Londres : The University of Chicago Press, 1973. 233 p. : il. - Dallal, Alberto (El Colegio de México A.C., 1974)
HASSAN FATHY, Architecture for the Poor, Chicago y Londres, The University of Chicago Press, 1973.